Career Breaks after Childbirth: The Impact of Family Leave Reforms in the Czech Republic - Alena Bičáková; Klára Kalíšková (Institute for the Study of Labor (IZA), 2016)
The Czech Republic is a country with a strong attachment of women to the labor market, but with one of the longest paid family leaves, which is often followed by a spell of unemployment. Using a difference-in-differences methodology, we study the impact of two reforms of the duration of the parental allowance on the labor market status of mothers 2-7 years after childbirth. While the 1995 reform prolonged the allowance from 3 to 4 years, the 2008 reform allowed some parents to shorten the duration of the allowance to only 2 or 3 years with an equivalent total monetary amount. We find that in response to the 1995 reform, 36% of mothers extended their family leave beyond the 3-year job protection period. The 2008 reform partially reversed this effect. Both reforms also had a considerable impact on post-leave unemployment and inactivity of mothers.
Keywords: J13; J18; J22; 330; unemployment; female labor supply; family leave; policy evaluation